Public Land Movement in Nepal: Expanding Coverage and Diminishing Achievements - Sapkota, Mahendra (New Angle: Nepal Journal of Social Science and Public Policy, 2016)
In many countries of the developing world, the dominant development discourse is being contested by the emergence of different kinds of social movements and the land rights movements in agrarian socieites is not an exception. Despite having a long historical background, critics suggest that the land governance is largely based on state-centric epistemology and less on the pro-poor discourse of movement and struggle. Building on this critique, this paper highlights different issues, challenges and opportunities of the land-based movements particularly in context of western Tarai region of Nepal. The central proposition of the paper is that there are some significant implications and research gaps to be analyzed under the emerging discourse of “land movement” in Nepal. It therefore argues that ‘public land management’ and ‘public land movement’ are two mutually contested phenomena with contradicting actors, strategies, policy gaps, empirical dilemmas and shifting of power dynamics.